Overview of Sri Lankan Publishing - Prabhashini, Kumesh (The World Association of Scientists & Professionals TWASP, United States, 2022)
The field of print publishing in Sri Lanka is exclusively for books, magazines and newspapers. Those expressions are categorized according to language, culture and religion. This paper explores the overview of Sri Lankan publishing history from Magazine history, book history, and Newspaper history. This study driven by the secondary data from the historical resources. It was revealed that Sri Lankan publishing historically developed for communicate the religious, cultural, political and human life communicate and according to impact of the Dutch and British colonial era formal publishing methods like books, magazines and newspapers came to the Sri Lankan society and it focused to communicate their empower rules and colonial politics. After the colonial era came the commercial publishing and it changed on time to time from the content and format.
Keywords: Publishing History; Newspaper Publishing; Magazine Publishing; Book Publishing; Sri Lanka